PREOPERATIVE PREDICTION OF WALL INVASION DEPTH OF PRIMARY TUMOR (PT) IN GASTRIC CANCER PATIENTS - M.YU. REUTOVICH; O.V. KRASKO; A.I. PATSEIKA; H.S. HUSSEIN (Паёми Сино)
Objective: To create a prognostic nomogram that evaluates the likelihood of serosal invasion of the primary tumor in the stomach wall (рТ4) by analyzing preoperative data. This model aims to optimize treatment plans and enhance the effectiveness of treatment for LAGC.